2007
DOI: 10.1038/ng1981
|View full text |Cite|
|
Sign up to set email alerts
|

A common coding variant in CASP8 is associated with breast cancer risk

Abstract: The Breast Cancer Association Consortium (BCAC) has been established to conduct combined case-control analyses with augmented statistical power to try to confirm putative genetic associations with breast cancer. We genotyped nine SNPs for which there was some prior evidence of an association with breast cancer: CASP8 D302H (rs1045485), IGFBP3 -202 C --> A (rs2854744), SOD2 V16A (rs1799725), TGFB1 L10P (rs1982073), ATM S49C (rs1800054), ADH1B 3' UTR A --> G (rs1042026), CDKN1A S31R (rs1801270), ICAM5 V301I (rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
392
4
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(419 citation statements)
references
References 28 publications
18
392
4
4
Order By: Relevance
“…24,25 Even though conflicting evidences have been presented, 26 this particular polymorphism has been associated with decreased risk of multiple cancers. 25,27 Similarly, a large study including 17 109 breast cancer patients (versus 16 423 controls) concluded that the CASP8 D302H polymorphism in some populations was associated with a reduced risk of breast cancer, 28 a correlation that has been confirmed also for other tumor types. 27 A CASP10 V410I substitution was also less frequently observed in patients suffering from breast cancer compared with control groups and the risk of carcinogenesis significantly decreased in individuals harboring a combination of these variant alleles, indicating a mutual protective effect.…”
Section: Casp Polymorphismmentioning
confidence: 95%
“…24,25 Even though conflicting evidences have been presented, 26 this particular polymorphism has been associated with decreased risk of multiple cancers. 25,27 Similarly, a large study including 17 109 breast cancer patients (versus 16 423 controls) concluded that the CASP8 D302H polymorphism in some populations was associated with a reduced risk of breast cancer, 28 a correlation that has been confirmed also for other tumor types. 27 A CASP10 V410I substitution was also less frequently observed in patients suffering from breast cancer compared with control groups and the risk of carcinogenesis significantly decreased in individuals harboring a combination of these variant alleles, indicating a mutual protective effect.…”
Section: Casp Polymorphismmentioning
confidence: 95%
“…However, with the efforts of the Breast Cancer Association Consortium in conducting candidate gene case -control association studies with enhanced statistical power by combining several breast cancer cohorts, two novel genes were identified, namely, CASP8 and TGFB1. 76 Recently, the success of genetic studies of breast cancer has also been seen in three studies 52 -54 and their findings are starting to shed some new light on the genetic basis of this cancer. With their three-stage study design and a sample size of more than 50 000 cases and controls, Easton et al 52 identified six highly significant SNPs.…”
Section: Breast Cancermentioning
confidence: 99%
“…23,24 Twenty-seven studies investigated the potential functional polymorphisms (19 for IGF1 (CA) n , 16 for IGFBP3 AÀ202C and 6 for IGFBP3 Gly32Ala), including 27 852 cases and 40 354 controls. One multicenter study 14 was included and two duplicated articles were excluded for the association between genotypes and cancer risk. 25,26 Nine studies were available for genotypephenotype correlation analysis.…”
Section: Identification and Eligibility Of Studiesmentioning
confidence: 99%